Prevalence of Hypothermia and Associated Factors Among Neonates Visiting Neonatal Intensive Care Unit, Asella Teaching and Referral Hospital, Asella, South East Ethiopia - Chiri, Abdureshid Kedir; Heyi, Sadat Kasim; Bidu, Kassahun Tegegne; Bieza Assegu, Yirga (British Journal of Healthcare and Medical Research, 2024)
Background: Hypothermia is the reduction in the body temperature (below 36.5°C). It is a global problem but it showed a higher prevalence in developing countries (>90%) and contributes to a substantial proportion of neonatal mortality. Objective: To assess the prevalence and associated factors of neonatal hypothermia among newborns admitted to the NICU of Asella Referral Hospital. Methods and Materials: Institution-based retrospective cross-sectional study was conducted from September to October 2022. The data was collected from mother and newborn charts using a semi-structured questionnaire. Data were cleaned, coded, entered in EPI-info version 7.2, and exported to Statistical Package for Social Sciences (SPSS) version 25 for analysis. Bivariate and multivariate logistic regression and crude and adjusted odds ratio with 95% confidence interval were computed. Variables that had a significant association in multivariate logistic regression were taken as a factor of neonatal hypothermia. Result: Of 189 neonates included in the study, 137 (72.4%) had neonatal hypothermia. Low birth weight (AOR=7.94; 95% CI: 27, 27.71), pre-term delivery (AOR=2.99; 95% CI: 1.73, 12.23), bathing the neonate before 24 hours (AOR=5.12; 95% CI: 1.02, 25.68), not starting breastfeeding within 1 hour of birth (AOR=4.09; 95% CI: 1.27, 13.23), no skin-to-skin contact immediately after birth (AOR=20.98; 95% CI: 1.69, 259.68), neonates who received CPR (AOR=4.17, 95% CI: 1.15, 15.02), and neonates born in a room not having radian heater (AOR=5.14; 95% CI: 2.03, 12.66) showed significant association with neonatal hypothermia. Conclusion: In this study, the proportion of hypothermia was high. Therefore, special attention is needed for the thermal care of preterm neonates, Low birth weight, and neonates receiving CPR. There should be strict adherence to WHO recommendations like warm resuscitation, skin-to-skin contact, breastfeeding within one hour, and delaying bathing of the neonate.